The Fundamental Idea for the Development of Tanjung Berlian International Port in Borneo as a Supporter of the National Capital Region - Sani, Abdul; Syadzali, Ahmad; Nuryadin, Nuryadin; Yulizar, M. Adriani (Journal of World Science, 2023)
This research aims to establish a fundamental policy framework and understand the community needs associated with the development of Tanjung Berlian Port in Borneo. The focus is on achieving cohesive development policies and ensuring sustainable, long-term impacts at the national level. The research methodology employed is a qualitative program research approach. The research focuses on the location of the site plan for a maritime event in the Lake River border area, extending to the Tanah Bumbu region for approximately 100 kilometers. The findings from the field research enable the continuation of international port development to support future National Connectivity Infrastructure (IKN) and become a strategic priority for enhancing the archipelago's geopolitical military defense and security. This research carries implications for crafting improved policies related to the development of Borneo's Tanjung Berlian Port to optimize its strategic potential in supporting National Connection Infrastructure, geographical, geopolitical, and state security interests. This research underscores the importance of developing Tanjung Berlian Port in Kalimantan as a key element in supporting the future National Capital of Connectivity (IKN). In the strategic context of the archipelago, this port is considered a vital asset capable of strengthening military defense and security, while also holding significant geopolitical importance for Indonesia. The research findings emphasize the need for better policy formulation to maximize the potential of this port. The proper and optimal development of Tanjung Berlian Port is expected to make a significant contribution to supporting national infrastructure and bolstering the overall geographical, geopolitical, and state security positions.